Platinum nanoparticles on reduced graphene oxide as peroxidase mimetics for the colorimetric detection of specific DNA sequence. Issue 23 (24th May 2016) - Chau, Li Yin; He, Qijin; Qin, Ailin; Yip, Shea Ping; Lee, Thomas M. H.
Abstract : We report the first demonstration of platinum nanoparticles–reduced graphene oxide nanocomposites as peroxidase mimetics for colorimetric DNA detection. Abstract : In this work, we developed a simple and sensitive colorimetric detection platform for specific DNA sequences by using peroxidase mimetics of platinum nanoparticles supported on reduced graphene oxide. This nanocomposite possessed the combined advantages of platinum nanoparticles (superior peroxidase-like activity) and reduced graphene oxide (π-stacking interaction with single-stranded but not double-stranded DNA). The catalytic activity was strongly dependent on the chloroplatinic acid-to-graphene oxide mass ratio during the synthesis step, with an optimum ratio of 7 : 1. Unlike natural peroxidase, the nanocomposite had excellent stability over wide ranges of temperature (4–90 °C) and pH (1–13). For DNA detection, the nanocomposite had higher affinity for the single-stranded probe (in the absence of target) than the probe–target duplex. The probe-bound nanocomposite was stabilized against salt-induced aggregation and thus upon the addition of 3, 3′, 5, 5′-tetramethylbenzidine and hydrogen peroxide to the supernatant, an intense blue color was generated. The linear range and limit of detection of this assay platform were 0.5–10 nM and 0.4 nM, respectively. Moreover, this platform featured high specificity that 3-base-mismatched sequence could be distinguished with the naked eye and 1-base-mismatched sequence with absorbance measurement. Furthermore, the applicability for real sample detection was demonstrated by polymerase chain reaction product analysis. Taken together, this new platform is well suited for point-of-care and on-site nucleic acid testing.